(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
E. Tesauro in his masterpiece Il Cannocchiale Aristotelico used the metaphor of theatre to describe rhetoric effects of metaphors. Moreover metaphor effects, in Tesauro, are mostly described in psychological and cognitive terms. W. Eggington (How the world became a stage, 2003) names theatricality the relationship between individual and space that appears since upon Sixteenth century in Western Europe theatre. This form of relationship takes the place of presence. Thus Eggington calls the form of theatre performance spread in the period before Sixteenth century. This paper takes into account Eggington hypothesis and discusses his validity. Moreover in order to understand the implications of the rhetoric of metaphor exposed in Tesauro’s masterpiece, the research compares metaphoric effects with the dynamic of theatricality.